1988
DOI: 10.1182/blood.v71.6.1726.1726
|View full text |Cite
|
Sign up to set email alerts
|

Decline in rates of clearance of IgG-sensitized erythrocytes with increasing age

Abstract: Decreased immune functions have been suggested as a cause for the increased incidence of autoimmunity, malignancy, and infection in the elderly population. To assess the possible role of changes in macrophage function in the aging process we studied the Fc receptor- mediated clearance of IgG-coated erythrocytes in 56 healthy normal volunteers by following the removal of radiolabeled autologous erythrocytes. An age-related decrease in Fc-mediated clearance rates in both female and male subjects was found, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1990
1990
1995
1995

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…However, complete heteropolymers, containing MAb to CR1 cross-linked with either human or mouse IgG, bind to primate erythrocytes and are cleared (26). Numerous in vivo studies indicate that IgG that is bound to erythrocytes via cell surface antigens causes the erythrocyte to be recognized and cleared by the RES (45,46), yet IgG that is bound to erythrocyte CR1 as part of a C3b-opsonized IC does not sensitize erythrocytes for clearance, but IC are cleared and removed from erythrocytes in the liver and spleen (19,20). In vitro experiments suggest that recognition of human IgG bound to primate erythrocytes via most cell surface antigens appears to be quite different from recognition of human IgG bound to erythrocyte CR1 in a C3b-opsonized IC (47).…”
Section: Discussionmentioning
confidence: 99%
“…However, complete heteropolymers, containing MAb to CR1 cross-linked with either human or mouse IgG, bind to primate erythrocytes and are cleared (26). Numerous in vivo studies indicate that IgG that is bound to erythrocytes via cell surface antigens causes the erythrocyte to be recognized and cleared by the RES (45,46), yet IgG that is bound to erythrocyte CR1 as part of a C3b-opsonized IC does not sensitize erythrocytes for clearance, but IC are cleared and removed from erythrocytes in the liver and spleen (19,20). In vitro experiments suggest that recognition of human IgG bound to primate erythrocytes via most cell surface antigens appears to be quite different from recognition of human IgG bound to erythrocyte CR1 in a C3b-opsonized IC (47).…”
Section: Discussionmentioning
confidence: 99%
“…The effect of age on phagocytes has previously been studied using a variety of methods (14,(39)(40)(41). Receptor number has been reported unaffected with age (42).…”
Section: F E M a L E M A L Ementioning
confidence: 99%
“…Macrophages show little dysfunction with age (44), and their function appears to be maintained in well-studied animal models, as well as in vitro (45,46). However, Melez et al (41) reported an age-related decrease in Fc-mediated clearance rates of IgG sensitized erythrocytes by splenic macrophages. Nagel et al (47) found the ability of PMNL to reduce nitroblue tetrazolium and to kill Staphylococcus aureus to be independent of age, but superoxide production by PMNL in response to latex particles was significantly lower in elderly adults.…”
Section: F E M a L E M A L Ementioning
confidence: 99%
“…However, the effects of aging on macrophages, which participate in a variety of host defence mechanisms, are quite contradictory. There are reports that macrophage-dependent host defence mechanisms are decreased [4][5][6], apparently unaffected [7] or even enhanced [8] with age.…”
Section: Introductionmentioning
confidence: 99%